Exploring the theory and ethics of autoethnographic social research with adult survivors of childhood sexual abuse (CSA) - McRobert, Korinna (Przegląd Krytyczny, 2024)
This paper is an outline of the current stand of a doctoral research project. The research in progress deals with the phenomenon of childhood sexual abuse (CSA) as an experience of those overpowered by it in the past: the survivors. It introduces on-going autoethnographic social research, on survivors of CSA by a survivor of CSA. The aim of the paper is to give an insight into the planning phase of doctoral research, i.e. a research project that has yet to do fieldwork. It sets the theoretical context and foundation of the study, contextualising the methodological approach chosen. The empowerment theory is used as the main theoretical orientation of the study. The methodological practice, still a work in progress, is qualitative and arts-based, using method triangulation. Through the use of method triangulation, peer debriefing and member checking, the researcher wishes to employ academic rigour to ensure validity of her future research results. Ethics of such ‘sensitive’ research are considered and ethical approaches are proposed, in order to strike a balance between protection and safety, as well as participation and visibility. This paper frames the act of abuse as an act of overpowering, and focuses on the subsequent process of empowerment, post-abuse. Engaging in autobiographical research with hybrid methodology, aiming at incorporating both intellectual and body memories, is argued to be a sensible way forward, when trying to understand the effects of potentially traumatic experiences on people and their bodies. This paper gives an insight into the process of research development, a snapshot of the journey of a novel researcher.